Chronic Energy Deficiency, Anemia as a Risk Factor for Low Birth Weight Babies in East Nusa Tenggara - Khrispina Owa (Poltekkes Kemenkes Kupang, 2019)
Background: Low birth weight (LBW) among infants is one cause of neonatal and infant mortality. The Indonesian Demographic and Health Survey (SDKI, 2012) indicated that the neonatal mortality rate in Nusa Tenggara Timur was as high as 26/1000 KH, 15% of which were caused by low birth weight. This study seeks tounderstand the relationship between risks to CED, anemia on the incidence of LBW in the district of Ende. Method: This study design was a case control with a total of 156 respondents in the district of Ende, 2015.Case studies were mothers giving birth to infant weighing < 2500 gram and case control was 78 mothers having infants of normal weight ≥ 2500 gram. Data was obtained from mother’s clinic examination cards, ANC records and indepth interviews. Data was analysed using bivariate (chi square) analysis and multivariate using logistic regression. Result: Study indicates that the risk factors for LBW in infants include age of mother<20 or ≥35 years with adjusted OR (AOR)=6.8 (95% CI: 1.87 to 25.0), birth spacing <2 years OR 6.5 (95% CI: 1, 78 to 24.2), CED with AOR=5,3(95%CI:1,38-21,0),maternal occupation OR of 4.6 (95% CI: 1, 44 to 14.9), anemia with AOR=4,2(95%CI:1,37-13,1),presence of concomitant diseases such as malaria OR 3.9 (95% CI: 1.21 to 12.7) and low quality of antenatal care OR 3.5 (95% CI: 1.11 to 11.3). Conclusion: Age of mother<20 or ≥35 years,birth spacing <2 years, CED,maternal occupation, anemia, presence of concomitant diseases such as malaria and low quality of antenatal care are risk factors for LBW in the District of Ende.